2021
DOI: 10.3390/ijms22168750
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Cleavage Dioxygenase Genes of Chimonanthus praecox, CpCCD7 and CpCCD8, Regulate Shoot Branching in Arabidopsis

Abstract: Strigolactones (SLs) regulate plant shoot development by inhibiting axillary bud growth and branching. However, the role of SLs in wintersweet (Chimonanthus praecox) shoot branching remains unknown. Here, we identified and isolated two wintersweet genes, CCD7 and CCD8, involved in the SL biosynthetic pathway. Quantitative real-time PCR revealed that CpCCD7 and CpCCD8 were down-regulated in wintersweet during branching. When new shoots were formed, expression levels of CpCCD7 and CpCCD8 were almost the same as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Decapitation causes the outgrowth of axillary buds, which has been confirmed in pea plants [ 24 ], Cremastra appendiculata [ 25 ], and Chimonanthus praecox [ 26 ]. In sunflowers, two axillary buds sprouted simultaneously after removing the shoot tips.…”
Section: Resultsmentioning
confidence: 96%
“…Decapitation causes the outgrowth of axillary buds, which has been confirmed in pea plants [ 24 ], Cremastra appendiculata [ 25 ], and Chimonanthus praecox [ 26 ]. In sunflowers, two axillary buds sprouted simultaneously after removing the shoot tips.…”
Section: Resultsmentioning
confidence: 96%
“…These results are consistent with a study on peanut seed development, which reported that lncRNAs participated in plant growth and development by regulating hormones ( Ma et al, 2020 ). CCD8 and TB1 are vital genes that are known to regulate axillary bud development ( Dong et al, 2017 ; Wang X. et al, 2021 ). In our preliminary experiment, the plants with overexpressed NtCCD8 had fewer axillary buds, whereas the plants with RNAi of NtTB1 had more axillary buds.…”
Section: Discussionmentioning
confidence: 99%
“…SLs biosynthesis and signaling have been extensively studied in the regulation of axillary bud development ( Lin et al., 2009 ; Vogel et al., 2010 ; Pasare et al., 2013 ; Wen et al., 2016 ; Ren et al., 2020 ). In particular, CCD8 (a synthetic SLs gene) mutation caused increased branching in tobacco ( Gao et al., 2018 ), and CpCCD8 overexpression reduces the branching in the Arabidopsis CCD8 mutant ( Wang et al., 2021 ). On account of low abundance of SLs, little is known about their inactivation at the catabolic level ( Snowden et al., 2005 ; Arite et al., 2007 ; Simons et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%